Local Delivery and Glioblastoma: Why Not Combining Sustained Release and Targeting? - Gazaille, Claire; Sicot, Marion; Saulnier, Patrick; Eyer, Joël; Bastiat, Guillaume (Frontiers in Medical Technology, 2021)
Glioblastoma is one of the most aggressive brain tumors and is associated with a very low overall median survival despite the current treatment. The standard of care used in clinic is the Stupp’s protocol which consists of a maximal resection of the tumor when possible, followed by radio and chemotherapy using temozolomide. However, in most cases, glioblastoma cells infiltrate healthy tissues and lead to fatal recurrences. There are a lot of hurdles to overcome in the development of new therapeutic strategies such as tumor heterogeneity, cell infiltration, alkylating agent resistance, physiological barriers, etc., , and few treatments are on the market today. One of them is particularly appealing because it is a local therapy, which does not bring additional invasiveness since tumor resection is included in the gold standard treatment. They are implants: the Gliadel® wafers, which are deposited post-surgery. Nevertheless, in addition to presenting important undesirable effects, it does not bring any major benefit in the therapy despite the strategy being particularly attractive. The purpose of this review is to provide an overview of recent advances in the development of innovative therapeutic strategies for glioblastoma using an implant-type approach. The combination of this local strategy with effective targeting of the tumor microenvironment as a whole, also developed in this review, may be of interest to alleviate some of the obstacles encountered in the treatment of glioblastoma.